Analisis Peran Manajemen Operasional dalam Pengelolaan Antrian Pelayanan di Instalasi Gawat Darurat - Mukriani, Mukriani; Djunaedi, Djunaedi; Wijayanti, Lumastari Ajeng; Rahman, Muhammad Arif (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Background: Long queues and waiting times exceeding the standard in the Emergency Department (ER) are indicators of low hospital operational efficiency. This problem not only impacts patient satisfaction but also the overall safety and quality of healthcare services. The role of operational management is crucial in addressing this issue through resource management, workflow, and the integrated use of information technology. Objective: This study aims to analyze the role of operational management in managing queues in the ER and identify factors influencing the effectiveness of this queuing system. Methods: The study used a quantitative-descriptive approach using observation, semi-structured interviews, and document review in the ER of RSUD X. The sample consisted of 30 patients and 10 medical personnel selected purposively. Data were analyzed descriptively and linked to operational management theory. Results: It was found that operational management contributes significantly to queue management, through the implementation of a triage system, scheduling of healthcare personnel, and the utilization of hospital information systems. However, challenges such as limited bed capacity, shortage of medical personnel, and lack of information system integration remain major obstacles. Conclusion: Optimizing operational management in the emergency department (ED) has been shown to improve service flow and reduce waiting times. Continuous evaluation of operational systems and strengthening of human resources and information technology capacity are recommended to improve the quality of emergency services.